El núcleo familiar y la educación de los alumnos de 6to. año de educación general básica, de la Unidad Educativa “Pedro Vicente Maldonado”, durante la emergencia sanitaria generada por el Covid -19. periodo lectivo 2021-2022 - Yucta Inca, Priscila Lizeth (2022)
The objective of this research is to investigate “The family nucleus and education of sixth- grade students’ year of Basic General Education, parallel “A,” of the “Pedro Vicente Maldonado” Educational Unit, during the health emergency generated by COVID-19. School period”, in order to identify the problems that were generated during the school year and provide solutions to them; To develop the previous work, the use of different methods was used, which allowed obtaining the collection of information to carry out the study of proposed variables and give the necessary support to the present investigation. That is why the methodology used is of a mixed type, together with the use of bibliographical and field research. For this, it was not necessary to calculate any sample since it was possible to work with the entire population, which amounts to seventy-one people who are distributed into thirty-five parents, and thirty-five students to whom it was applied surveys a teacher was interviewed. With this, it was possible to obtain fundamental data on the problems that the new virtual modality has brought and the contribution that parents have had to their children in the educational process; In addition to this, through the theoretical and scientific foundation, the relationship between the assistance of the family and education in times of pandemic was established in the sixth- year students of the “Pedro Vicente Maldonado” Educational Unit.